Streptococcus mutans supernatant affects the virulence of Candida albicans - Garcia, Maíra Terra [UNESP]; dos Santos, Jéssica Diane [UNESP]; do Carmo, Paulo Henrique Fonseca [UNESP]; Mendes, Gabriela Vieira [UNESP]; de Oliveira, Jonatas Rafael; de Oliveira, Luciane Dias [UNESP]; Junqueira, Juliana Campos [UNESP] (Springer Nature, 2024)
Candida albicans causes a variety of clinical manifestations through multiple virulence factors that act simultaneously to overcome the immune system and invade the host tissues. Owing to the limited number of antifungal agents available, new candidiasis therapeutic strategies are required. Previous studies have demonstrated that the metabolites produced by Streptococcus mutans lead to a decrease in the number of Candida cells. Here, for the first time, we evaluated whether the C. albicans cells that survived the pretreatment with S. mutans supernatant can modify their virulence factors and their capability to infect Galleria mellonella larvae. Streptococcus mutans supernatant (SM-S) was obtained by filtering the culture supernatant of this bacterium. Then, C. albicans cells were pretreated with SM-S for 24 h, and the surviving cells were evaluated using in vitro and in vivo assays. The C. albicans pretreated with SM-S showed a significant inhibition of hyphal growth, an altered adhesion pattern, and an impaired capability to form biofilms; however, its proteolytic activity was not affected. In the in vivo assays, C. albicans cells previously exposed to SM-S exhibited a reduced ability to infect G. mellonella and a higher amount of circulating hemocytes. Thus, SM-S could inhibit important virulence factors of C. albicans, which may contribute to the development of new candidiasis therapeutic strategies.
Keywords: Antifungal metabolites; Candida albicans; Candidiasis; Galleria mellonella; Streptococcus mutans; Virulence factors